PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR PKn KELAS V SD NEGERI 011 BUKIT GAJAH KECAMATAN UKUI - Jasman R (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this research stems from low Civics (PKn) learning outcomes, characterized by an average student score of 67.2, which is below the established Minimum Completeness Criteria (KKM) of 75. Furthermore, only 9 students, or 37.80%, achieved complete study results. Based on this, the researchers aimed to improve learning through action research by applying the Student Teams Achievement Divisions (STAD) cooperative learning model. This study was conducted over two cycles, each consisting of two meetings and one daily test. The subjects were fifth-grade students of SD Negeri 011 Bukit Gajah. Data collection techniques included observation of teacher and student activities, as well as Civics test results. The study indicates that the implementation of the STAD cooperative learning model can improve student learning outcomes in Civics. This is evidenced by: (a) the activities of teachers increasing in each cycle. In the first cycle, the teacher's activity in the first meeting received a score of 15, or 62.5%, categorized as